Effect Of Work Ability and Discipline on Employee Performance (Study at PT. Binuang Mitra Bersama) - Rano Rano; Abdul Kadir (Hut Publication Business and Management, 2022)
The need for an ability or skill and discipline in a company is needed for now where all things about performance create new values ​​carried by the current and wave of technology and global media. The purpose of this study is to find out an overview of the ability and work discipline on employee performance, in addition to knowing the influence of ability and work discipline partially and simultaneously on employee performance. The study used the Explanatory Research method with a quantitative approach and data collection techniques through questionnaires. The sample used was 40 permanent employees at the company. Analysis of the data used is descriptive analysis method and inferential analysis by paying attention to the classical assumption test and multiple linear analysis. The results showed that work ability and work discipline had an effect on employee performance. Meanwhile, based on the calculation of the coefficient of termination (r2) that Ability and Work Discipline affect employee performance by 85.4% and the remaining 14.6% is influenced by other factors. From the statistical calculation of the Analysis of Variance Test (ANOVA) it is known that Fcount = 108.285 compared to F0.05;35 = 3.23 then Fcount > F0.05;35, so it can be stated that Ability and Work Discipline have a significant effect on Employee Performance and Simultaneously, Work Ability has a more dominant effect than Work Discipline on Employee Performance.